A Comparison of Hydrochloric Acid and Acetate Buffer Media for Trace Metal Analysis Using Sb-Film Electrodes: A Detailed Electrochemical Impedance Spectroscopy Study. Issue 4 (1st January 2019) - Finšgar, Matjaž; Xhanari, Klodian; Petovar, Barbara
Abstract : The main focus of this work is a detailed electrochemical impedance spectroscopy (EIS) study at different potentials of an in situ-prepared antimony-film modified electrode (SbFE) in either 0.01 M HCl or 0.1 M acetate buffer solutions. No such detailed EIS study has been presented previously. First, method validation in terms of detection and quantification limits (LOD and LOQ respectively), linear concentration range, accuracy, and precision was performed for the bare glassy carbon electrode (GCE) and in situ-formed SbFE in both media employed in the determination of trace amounts of Zn(II), Cd(II), and Pb(II). Next, by means of EIS, the performance of these electrodes was explained by investigating the electrode's behavior at certain potentials that are crucial in anodic stripping voltammetry experiments. The method sensitivity was explained by the polarization resistance values obtained from the detailed EIS fitting procedure. Furthermore, a combination of charge-transfer-controlled and diffusion-controlled processes was taken into account. It was shown that the behavior of these electrodes strongly depends on the medium used, on the potential applied, and on the presence of certain species in the solution. Potentials of zero charge were also evaluated for the bare GCE and SbFEs in both solutions.